Identification of Fatty Acid-Binding Protein 4 as a Potential Biomarker and Therapeutic Target for Antineutrophil Cytoplasmic Antibody-Associated Glomerulonephritis - Lu Cheng; Qian Ren; Jing Liu; Mei-Lian Yu; Rong-Shuang Huang; Fan Guo; Liang Ma; Shen-Ju Gou; Ping Fu (Kidney Diseases)
Introduction: Fatty acid-binding protein 4 (FABP4) is a novel adipokine that is critically involved in many inflammatory and immune diseases. However, the role of FABP4 in antineutrophil cytoplasmic antibody (ANCA)-associated glomerulonephritis (ANCA-GN) remains unclear. The current study aimed to investigate the role of FABP4 in patients with ANCA-GN. Methods: Plasma and urine samples from 37 patients with active ANCA-GN and kidney biopsy specimens from another group of 56 patients with ANCA-GN were collected. The plasma and urinary levels of FABP4 were measured by enzyme-linked immunosorbent assay and the kidney FABP4 expression was determined by immunohistochemistry and immunofluorescence staining. Associations between FABP4 levels with clinical and pathologic parameters were analyzed. To further elucidate the role of FABP4 in ANCA-GN, a novel FABP4 inhibitor, BMS309403, was employed in a recognized rat model of experimental autoimmune vasculitis (EAV). Results: Plasma and urinary levels of FABP4 in active ANCA-GN patients were significantly higher than those in normal controls {52.8 ± 23.6 ng/mL vs. 16.9 ± 8.8 ng/mL, p < 0.01; median 126.6 (interquartile range [IQR] 28.4–311.2) ng/g Cr vs. median 0.0 (IQR 0.0–0.0) ng/g Cr, p < 0.01, respectively}. Immunohistochemical analysis revealed higher glomerular and tubular expression of FABP4 in the kidneys of ANCA-GN patients than those in normal controls (0.015 ± 0.012 vs. 0.004 ± 0.003, p < 0.001; 0.053 ± 0.026 vs. 0.011 ± 0.010, p < 0.001, respectively). Moreover, for ANCA-GN patients, urinary FABP4 levels were significantly higher in active ANCA than those in remission (184.3 ± 187.0 ng/g Cr vs. 9.4 ± 23.9 ng/g Cr, p < 0.01). Correlation analysis showed that urinary levels of FABP4 correlated with serum creatinine (r = 0.596, p < 0.0001), urinary albumin/Cr (r = 0.523, p = 0.001), blood neutrophil ratio (r = 0.386, p = 0.018), PT (r = 0.583, p = 0.001), APTT (r = 0.364, p = 0.034), hemoglobin level (r = -0.398, p = 0.015), estimated glomerular filtration rate (r = -0.680, p < 0.0001), crescent proportion (r = 0.661, p = 0.032), and all-cause death of ANCA-GN patients (HR 2.93, 95% CI [1.05–8.19]). Furthermore, FABP4 inhibition by BMS309403 ameliorated renal injury in a rat mole of ANCA-GN. Conclusions: Urinary FABP4 levels might reflect the disease activity and renal involvement of ANCA-associated vasculitis, and FABP4 might act as a promising therapeutic target against ANCA-GN.